2020
DOI: 10.1002/ddr.21776
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin alleviates d‐GalN/LPS‐induced acute liver injury by inhibiting NLRP3 inflammasome

Abstract: Acute liver injury (ALI) is a serious syndrome that is associated with high mortality, but there are few effective treatments. The activation of NLRP3 inflammasome is associated with ALI. Oridonin is a natural substance with an anti-inflammatory effect and has been reported to be an inhibitor of NLRP3. The aim of this study was to investigate the protective effect of oridonin on D-galactosamine (D-GalN)/lipopolysaccharide (LPS)-induced ALI and whether the effect is mediated by NLRP3. Mice were pretreated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Recent studies have shown that oridonin possesses strong therapeutic properties and limited side effects 15 . For instance, administration of oridonin protects against inflammation, including lipopolysaccharide (LPS)‐induced liver injury, lung inflammation, rheumatoid arthritis and so on 16–18 . There are also studies implying that oridonin can improve the lipid modulation in cancer and non‐alcoholic fatty liver 19,20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that oridonin possesses strong therapeutic properties and limited side effects 15 . For instance, administration of oridonin protects against inflammation, including lipopolysaccharide (LPS)‐induced liver injury, lung inflammation, rheumatoid arthritis and so on 16–18 . There are also studies implying that oridonin can improve the lipid modulation in cancer and non‐alcoholic fatty liver 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“… 15 For instance, administration of oridonin protects against inflammation, including lipopolysaccharide (LPS)‐induced liver injury, lung inflammation, rheumatoid arthritis and so on. 16 , 17 , 18 There are also studies implying that oridonin can improve the lipid modulation in cancer and non‐alcoholic fatty liver. 19 , 20 Moreover, a current clue also points out that oridonin exerts molecular function on stimulating LXRα in hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, limited research has suggested that ORI may contribute to improving the pathophysiology of NAFLD by exerting anti-inflammatory effects via the NLR family pyrin domain containing 3 (NLRP3) interaction or ROS-NF-κB suppression [ 27 , 28 ]. Our previous study also reported that ORI ameliorated acute liver injury-induced liver inflammation by inhibiting the NLRP3 inflammasome [ 29 ]. However, the function of ORI restoring lipid homeostasis to ameliorate hepatosteatosis and NAFLD, especially its exact molecular mechanism, has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…As a covalent NLRP3‐inflammasome inhibitor, oridonin (Ori) has anti‐inflammatory (He et al, 2018), anticancer (X. Liu et al, 2021), anti‐oxidation (L. Li et al, 2021), and anti‐sepsis (Y. J. Zhao et al, 2016) properties. Ori protects against carbon tetrachloride (CCl 4 ) (D. Liu et al, 2020) and ALI induced by LPS/ d ‐GalN (Deng et al, 2017; T. Zhang et al, 2021) and bisphenol A (X. Wang et al, 2021). Previously study found that Ori regulates intestinal flora and the hepatic urea cycle to reduce APAP‐induced liver injury (Hong et al, 2021), but the underlying molecular mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%